Moving the lenses of trauma — Trauma-informed care in the burns care setting. Issue 6 (September 2020) - Cleary, Michelle; West, Sancia; Kornhaber, Rachel; Visentin, Denis; Neil, Amanda; Haik, Josef; Kezelman, Cathy; McLean, Loyola
Highlights: Trauma itself, has been found to contribute to a range of mental health conditions. Coping mechanisms for trauma include addiction, self-harm and suicidal ideation. Understanding coping mechanisms supports trauma-informed interventions. Trauma-informed care supports recovery and minimises risk of re-traumatisation. Trauma-informed care in burns is vital to in-service delivery. Abstract: Trauma impacts people's coping mechanisms with their ability to function posing risks to their capacity to manage and respond appropriately to stressors, and to recover. Trauma informed care recognises the needs of survivors by focusing on system-wide design and support during recovery, minimising the risk of re-traumatisation, and maximising choice and empowerment for new adaptations and post-traumatic growth. The principles of TIC are currently not being fully utilised in burns practice, including for severe burns, with the nature, extent and impacts of trauma not being fully understood or acknowledged. Those who sustain a burn injury have an increased risk for developing psychosocial issues that can extend to the family unit, and people with pre-existing mental disorders are more likely to sustain a burns injury, experiencing extended hospitalisation and rehabilitation and being less likely to adhere to burns care. With the application of trauma-informed care within the burns setting, along with an understanding and acknowledging the link between trauma, burns injuries and mental health, health care professionals can minimise potential negative psychological impacts. Investing resources is now essential to effectively address the "trauma deficit" in the area of burns recovery.